Discovery and characterization of novel cysteine-rich peptides in medicinal plants - Tan, Wei Liang (2018)
Small molecules and proteins represent two major families of pharmaceuticals used clinically. In between these two families, in terms of molecular size, are the disulfide-constrained peptides, a class of compounds that have their drug-like advantages of both small molecules and proteins. Disulfide-constrained peptides share the advantages of proteins for high on-target specificity and low off-target adverse side effects. They also have the robustness of small molecules to tolerate thermal, chemical and enzymatic degradation. Currently, naturally-occurring constrained peptides in plants are an underexplored chemical space in drug discovery. The objective of my thesis is the discovery and characterization of novel cysteine-rich peptides in medicinal plants. They include Lycium babarum, the plant which produces wolfberries, the popular functional food and herb, from which a novel carboxypeptidase inhibitor and a new class of cysteine-rich peptides, lybatides containing a disulfide-stapled helix, were isolated. The wolfberry carboxypeptidase inhibitor inhibits the activity of carboxypeptidase A comparable to the potato carboxypeptidase inhibitor and may account for the anti-thrombotic effect usually associated to wolfberry. In contrast, lybatides isolated from the root bark of the same tree display a structure of naturally-occurring stapled peptides. This shows that one plant is able to produce different cysteine-rich peptides. In Eurycoma longifolia, commonly known as Tongkat Ali a popular aphrodisiac in Malaysia, a novel 10C-heveinlike peptide, elongtide 1, was isolated and characterized. The structure and disulfide connectivity of eL1 was determined, confirming the previously predicted disulfide connectivity of the 10C-hevein-like peptide subclass. Together, my thesis expands the existing knowledge of cysteine-rich peptides and enriches the number of existing disulfide-constrained peptide scaffolds for drug design and peptidyl therapeutic development.